Glutamate Transporter GLT1 Expression in Alzheimer Disease and Dementia With Lewy Bodies - Garcia-Esparcia, Paula; Diaz-Lucena, Daniela; Ainciburu, Marina; Torrejón-Escribano, Benjamin; Carmona, Margarita; Llorens, Franc; Ferrer, Isidro (Frontiers in Aging Neuroscience, 2018)
Glutamate transporter solute carrier family 1, member 2 (GLT1/EAAT2), a major modulator of glutamate homeostasis in astrocytes, is assessed in post-mortem human brain samples of frontal cortex area 8 in advanced stages of Alzheimer disease (AD) and terminal stages of dementia with Lewy bodies (DLB) in order to gain understanding of astrogliopathy in diseases manifested by dementia. Glial fibrillary acidic protein (GFAP) mRNA expression is significantly increased in AD but not in DLB, whereas GLT1, vesicular glutamate transporter 1 (vGLUT1) and aldehyde dehydrogenase 1 family member 1 (ALDH1L1) are not modified in AD and DLB when compared with controls. GLT1 protein levels are not altered in AD and DLB but GFAP and ALDH1L1 are significantly increased in AD, and GFAP in DLB. As a result, a non-significant decrease in the ratio between GLT1 and GFAP, and between GLT1 and ALDH1L1, is found in both AD and DLB. Double-labeling immunofluorescence and confocal microscopy revealed no visible reduction of GLT1 immunoreactivity in relation to β-amyloid plaques in AD. These data suggest a subtle imbalance between GLT1, and GFAP and ALDH1L1 expression, with limited consequences in glutamate transport.